Analisis Sensori Smoothies dengan Penambahan Chia Seeds sebagai Pangan Tinggi Serat - Paramita, Farah; Katmawanti, Septa; Kurniawan, Agung; Komariyah, Putri Nurul; Sabrina, Maurizka; Samah, Dea Aflah (Preventia: The Indonesian Journal of Public Health, 2020)
Obesity is one of triple burden malnutrition faced by Indonesia. Consuming balance nutrition throughadequate intake of vegetables and fruits as a source of fiber is recommended to prevent obesity. Smoothies could be way to enjoy vegetables and fruits to provide adequate intake of fiber.There is one food ingredient that has recently become concern for research called chia seeds. Chia seeds are high in fiber, mineral, vitamin and also great source of unsaturated fatty acids. This study was performed in to develop smoothies with addition of chia seeds(0 grams, 2.5 grams, 5 grams and 7.5 grams)thatevaluatedusing sensory analysis to investigate level of preference for taste, aroma, color and thickness. This was a quantitative study with experimental design using 4 treatments. Organoleptic test was performed by 35 panelists to determine preference on sensory attributes such as taste, aroma, color and thickness smoothies. Anova statistical test were performed to investigate the different panelis preference of sensory attributes. Statistical test showed that there was no significant different in sensory attributes taste and thickness (p > 0.05) and there was a significant differentin sensory attribues color and aroma between 4 treatment of smoothies(p<0.05). The addition of chia seeds in smoothies have an effect on level preverence on color and aroma. Panellist preferedsmoothies without addition of chia seeds forsensory attributes taste, color and aromaand addition of 5 grams chia seeds for sensory attributes thickness.